Repurposing non-antifungal drugs auranofin and pentamidine in combination as fungistatic antifungal agents against C. albicans - Lin, Jiaying; Xiao, Xueyi; Liang, Yijing; Zhao, Huimin; Yu, Yingxiao; Yuan, Peiyan; Lu, Sha; Ding, Xin (Frontiers in Cellular and Infection Microbiology, 2022)
Fungal infection is a serious global health issue, causing approximately 1.5 million mortalities annually. However, clinically available anti-fungal drugs are limited, especially for multidrug-resistant fungal infections. Therefore, new antifungal drugs are urgently needed to address this clinical challenge. In this study, we proposed two non-antifungal drugs, auranofin and pentamidine, in combination to fight against multidrug-resistant C. albicans. The insufficient antifungal activity of anti-rheumatic drug auranofin is partially due to fungal membrane barrier preventing the drug uptake, and anti-protozoal drug pentamidine was used here to improve the permeability of membrane. The auranofin/pentamidine combination displayed synergistic inhibitory effect against both drug-susceptible and drug-resistant C. albicans, as well as biofilm, and significantly reduced the minimum inhibitory concentration of each drug. At non-antifungal concentration, pentamidine can disrupt the membrane integrity and increase membrane permeability, leading to enhanced cellular uptake of auranofin in C. albicans. This repurposing strategy using the combination of non-antifungal drugs with complementary antifungal mechanism may provide a novel approach for discovery of antifungal drugs to fight against multidrug-resistant fungal infections.